Resveratrol Improves Heart Function by Moderating Inflammatory Processes in Patients with Systolic Heart Failure - Roland Gal; Laszlo Deres; Orsolya Horvath; Krisztian Eros; Barbara Sandor; Peter Urban; Szilvia Soos; Zsolt Marton; Balazs Sumegi; Kalman Toth; Tamas Habon; Robert Halmosi (MDPI AG, 2020)
The effects of resveratrol (RES) in heart failure have already been evaluated in animal models; however, in human clinical trials, they have not been confirmed yet. The aim of this study was to assess the effects of resveratrol treatment in systolic heart failure patients (heart failure with reduced ejection fraction or HFrEF). In this human clinical trial, 60 outpatients with NYHA (New York Heart Association) class II-III HFrEF were enrolled and randomized into two groups: receiving either 100-mg resveratrol daily or placebo for three months. At the beginning and at the end of the study echocardiography, a six-minute walk test, spirometry, quality of life questionnaire, lab test and RNA profile analysis were performed. The systolic and diastolic left ventricular function, as well as the global longitudinal strain, were improved significantly in the resveratrol-treated group (RES). Exercise capacity, ventilation parameters and quality of life also improved significantly in the RES group. In parallel, the cardiac biomarker levels (N-terminal prohormone of brain natriuretic peptide (NT-proBNP) and galectin-3) decreased in the treated group. The level of inflammatory cytokines decreased significantly after RES supplementation, as a consequence of the decreased expression level of leucocyte electron transport chain proteins. The main findings of our trial are that RES treatment added to the standard heart failure therapy improved heart function and the clinical condition by moderating the inflammatory processes in patients with HFrEF.